2011
DOI: 10.1208/s12249-011-9667-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Powder Blend Homogeneity Using Light-Induced Fluorescence

Abstract: Abstract. Light-induced fluorescence (LIF) was evaluated as a process analytical technology to monitor blend homogeneity and establish a relationship with high-performance liquid chromatography (HPLC). Secondary aims for this study included a determination of blend steady-state, acceptable mixing time interval, and mixing end point. Also, identification of potential "dead spots" in the 124 L intermediate bulk container mixing tote was explored. Individual samples from 13 sample locations were collected at 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Among the variety of tools, particular attention was paid to the methods using the fluorescence phenomenon and image analysis. These instruments are used in the following industrial sectors: food, agricultural, pharmaceutical and chemical industries (Berthiaux et al, 2006, Coppeta et al, 1995Dauman et al, 2008;Karumanchi et al, 2011;Lai et al, 2001;Matuszek, 2015;Realpe et al, 2003;Zelko et al, 2012).…”
Section: Shorter Communicationmentioning
confidence: 99%
“…Among the variety of tools, particular attention was paid to the methods using the fluorescence phenomenon and image analysis. These instruments are used in the following industrial sectors: food, agricultural, pharmaceutical and chemical industries (Berthiaux et al, 2006, Coppeta et al, 1995Dauman et al, 2008;Karumanchi et al, 2011;Lai et al, 2001;Matuszek, 2015;Realpe et al, 2003;Zelko et al, 2012).…”
Section: Shorter Communicationmentioning
confidence: 99%
“…Homogeneity of the final blend after mixing depends on many Page 8 of 43 A c c e p t e d M a n u s c r i p t 7 parameters such as mixing method, mixer operating parameters, and component concentrations [27][28][29]. The tendency of a powder mixture to either form a consistent blend or to separate depends mostly on physical properties such as cohesiveness, particle size distribution, particle density, electrostatic charge and other surface properties [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…High-performance liquid chromatography has been widely used as a standard off-line reference method for homogeneity analysis [44,45]. Non-invasive techniques such as near-infrared (NIR) spectroscopy [46][47][48][49][50][51][52] and chemical imaging [53][54][55], Raman spectroscopy [56][57][58], and lightinduced fluorescence [31,59] are also widely used for on-line or in-line measurement of blend uniformity. Of the large number of publications describing such techniques for blend uniformity Page 9 of 43 A c c e p t e d M a n u s c r i p t 8 analysis, however, few have noted the impact of effective sample volume on homogeneity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that LIF can be used in pharmaceutical blending to determine the blending end point (1,10). Karumanchi et al (10) used off-line LIF to determine blend uniformity, mixing end point, and identification of mixer dead-spots for a commercial scale blending operation. This technique has also shown to be promising in nondestructively measuring online active pharmaceutical ingredient (API) tablet concentration (11,12).…”
Section: Introductionmentioning
confidence: 99%